CADANGAN KARBON TANAH PADA BERBAGAI TINGKAT KERAPATAN TAJUK DI HUTAN LINDUNG KEBUN KOPI DESA NUPABOMBA KECAMATAN TANANTOVEA KABUPATEN DONGGALA - S, Muardimansah; Akhbar, Akhbar; Arianingsih, Ida (Jurnal Warta Rimba, 2016)
One of the preserve forest in Central Sulawesi is a preserve forest kebun kopi located in the Nupabomba Village, Tanantovea, Donggala District with area 1591,1 ha. This study aims to estimate soil carbon stocks at different levels of canopy density in the preserve forest, Kebun Kopi, Nupabomba Village, Tanantovea, Donggala District using satellite imagery and Geographic Information System (GIS). The method used NDVI analysis serves to determine the level of canopy density. Determination of sample plots is done intentionally based on the image that represents the level of canopy density with size of each land type: 20 m x 100 m. in determination of organic carbon content, the method used is the method of Walkley and Black. Result from this study showed total soil carbon are stored at various levels in the preserve forest canopy density Kebun Kopi in Nupabomba Village is 103.047,26 tons. In the area areas with sparse canopy, found soil carbon stocks are 27,12 tons/ha with the area of 196,7 ha and soil carbon number reached 5334,50 tons. In the area with sparse canopy found reserve of soil carbon contained 69,25 tons/ha with the area of 755,2 ha, soil carbon reaches 52.297,6 tons. Whereas the tight canopy area found reserve of soil carbon contained 71,05 tons/ha with the area of 639,2 ha and soil carbon number reached 45.415,16 tons.Key words: soil carbon, NDVI, Preserve Forest Kebun Kopi